2015
DOI: 10.1007/s11665-015-1583-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phase Transformation Conditions on the Microstructure and Tensile Properties of Ti-3Al-15Mo-3Nb-0.2Si Alloy

Abstract: The influence of phase transformation conditions (a/b solution treatment plus aging, b solution treatment plus aging, and b solution treatment plus duplex aging) on the microstructure and tensile properties of Ti-3Al-15Mo-3Nb-0.2Si alloy was studied. Microstructure observation indicates that the primary a phase, which formed during a/b solution treatment, can effectively limit the growth of the b grains. The alloy was heat treated in the a/b solution, which together with aging, formed smaller grains and finer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Therefore, "side plates" promote grain boundary strengthening to improve the strength level of the alloy [35]. Similar behavior was also observed in previous studies on Ti-55531 and Ti-3Al-15Mo-3Nb-0.2Si alloys [11,36]. Moreover, the density of the α phase that precipitated from the grain boundaries in the alloy increased with the rise in solution temperature.…”
Section: Phase Compositions and Microstructures Of The Samples After supporting
confidence: 84%
“…Therefore, "side plates" promote grain boundary strengthening to improve the strength level of the alloy [35]. Similar behavior was also observed in previous studies on Ti-55531 and Ti-3Al-15Mo-3Nb-0.2Si alloys [11,36]. Moreover, the density of the α phase that precipitated from the grain boundaries in the alloy increased with the rise in solution temperature.…”
Section: Phase Compositions and Microstructures Of The Samples After supporting
confidence: 84%
“…Meanwhile, the corresponding thermodynamic, and kinetic models were established, respectively. Xu et al (2015) investigated the effect of various heat treatments on phase transition mechanism, microstructural features, and room temperature mechanical properties for the TB8 alloy. They found that the location and morphological features of precipitates are closely related to the aging temperature and time.…”
Section: Introductionmentioning
confidence: 99%
“…Angelier 7 reported mechanisms for the β → α transformation during the aging process of metastable β titanium alloys. The α precipitates could be classified as three types, namely α GB , α WGB and α WM , according to their nucleation and growth during aging treatment 8,9 .…”
Section: Introductionmentioning
confidence: 99%